??THE DEFECT STRUCTURE OF (Fel - XCO)2 RE COMPOUNDS (RE = Gd AND Tb) (Biological Sciences - PJSIR, 1994)
Constitutional investigations of Fe-RE, Co-RE and Fe-Co-RE systems revealed that it requires an "RE" content inexcess of (Fe] - x Cox)z RE composition in orderto prepare these compounds free from the presence of phases. A comparisonof experimental and theoretical densi ties (calculated from the volumes of the unit cells) showed that the numberofvacantTM (TM=Fe, Co or Fc--Co) sites vary from 7.5% for (Feo.32COo.6s)Pd to 2.5% in the binary Fe.Gd compound.Likewise, there are 7.1 % such sites in (FeO.33 COO.67)Z Tb and 3.8% in the binary Coz Tb compound. Thus, it was concludedthat the defects in the lattices of these compounds, responsible for the deviation from ideal stoichiometric compositionsare vacancies on Fe and Co sites in respective binary compounds and on Fe+Co sites in ternary compounds.